The temporal pattern and lifestyle associations of respiratory virus infection in a cohort study spanning the first two years of life - Elizabeth Powell; Edward Sumner; Alex G. Shaw; Ronan Calvez; Colin G. Fink; J. Simon Kroll (BMC, 2022)
Abstract Background Respiratory virus infection is common in early childhood, and children may be symptomatic or symptom-free. Little is known regarding the association between symptomatic/asymptomatic infection and particular clinical factors such as breastfeeding as well as the consequences of such infection. Method We followed an unselected cohort of term neonates to two years of age (220 infants at recruitment, 159 who remained in the study to 24 months), taking oral swabs at birth and oropharyngeal swabs at intervals subsequently (at 1.5, 6, 9, 12, 18 and 24 months and in a subset at 3 and 4.5 months) while recording extensive metadata including the presence of respiratory symptoms and breastfeeding status. After 2 years medical notes from the general practitioner were inspected to ascertain whether doctor-diagnosed wheeze had occurred by this timepoint. Multiplex PCR was used to detect a range of respiratory viruses: influenza (A&B), parainfluenza (1-4), bocavirus, human metapneumovirus, rhinovirus, coronavirus (OC43, 229E, NL63, HKU1), adenovirus, respiratory syncytial virus (RSV), and polyomavirus (KI, WU). Logistic regression and generalised estimating equations were used to identify associations between clinical factors and virus detection. Results Overall respiratory viral incidence increased with age. Rhinovirus was the virus most frequently detected. The detection of a respiratory virus was positively associated with respiratory symptoms, male sex, season, childcare and living with another child. We did not observe breastfeeding (whether assessed as the number of completed months of breastfeeding or current feed status) to be associated with the detection of a respiratory virus. There was no association between early viral infection and doctor-diagnosed wheeze by age 2 years. Conclusion Asymptomatic and symptomatic viral infection is common in the first 2 years of life with rhinovirus infection being the most common. Whilst there was no association between early respiratory viral infection and doctor-diagnosed wheeze, we have not ruled out an association of early viral infections with later asthma, and long-term follow-up of the cohort continues.